Preventional audit: Implementation of SOX control to prevent fraud - Karina Nazarova; Viktoriia Mysiuk; Volodimir Gordopolov; Viktor Koval; Irena Danilevičienė (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The Euro-integration vector of Ukraine economic development and business in the open economy zone expands the economic and social potential of domestic enterprises and requires the formation of a reliable information environment to ensure the corporate interests of their investors (in the first) and other users of information (in particular). Today, corporate fraud is the most widespread form of economic crime in Ukraine and the world, which affects about 48% of domestic enterprises. The study attracted substantiated attention to the negative tendency towards the growth of economic crime in Ukraine, which in the end focuses on the fact that domestic business should apply a set of measures to withdraw part of the business from the "shadow economy". As a result, such measures will help increase the attractiveness of Ukraine's business investment. The study systematized and analyzed the progressive experience of developed countries, in the first place, the United States, in the fight against economic fraud. The study provides all grounds for asserting that it is quite feasible to achieve the tangible reduction of economic (financial) fraud with preventive measures (which is rather quick and effective). It is proved that the lack of aspirations of the enterprise management to overcome fraud leads to the formation of new money laundering schemes, and not control mechanisms - prevention of opportunities for committing fraud.
Keywords: C58; F30; G38; 650; audit; compliance-audit SOX; financial control; fraud; internal audit; internal control; SOX